Pengaruh Health Education Perawat IGD Tentang Penurunan Kesadaran Pada Pasien Terhadap Pengetahuan Keluarga Pasien Di IGD RSU Manado Medical Center - Alfrida Lulage; Suwandi Luneto; Silvia Dewi Mayasari Riu (Pusat riset dan Inovasi Nasional, 2024)
Loss of consciousness is a common problem in the health world. This situation dominates the Emergency Guard Unit in the hospital service. Unconsciousness is a mental and behavioral condition of decreased comprehension, coherence, and motivational capacity. As a result of the loss of consciousness in the patient that occurs, sometimes the family does not know when an unwanted situation occurs because of something that happens and resulting in that loss of awareness occurs. The aim of this study is to find out the impact of IGD nurses' health education on the decline in patient awareness on the knowledge of the patient's family at the IGD RSU Manado Medical Center. Research uses experimental research methods using one group research design pretest-posttest design. Sample of 15 respondents using purposive sampling. Data collection using questionnaires. Analysed with Mc Namer's statistical test. Gender survey results most female respondents 8 (53.3%), age most 17-25 years and 26-35 years 6 respondents (40,0%), most college education 8 respondents (53,3%), most employment private employees 7 respondents (46.7%). The Mc Namer test results are given a p value of 0,000 where < α 0.05. The conclusion in this study is that there is an influence of health education nurses IGD on decreased awareness in patients to the knowledge of the family of patients at IGD RSU Manado Medical Center. The recommendation is that the hospital should pay attention to health education for families, especially in the IGD room.